What drives the German current account? And how does it affect other EU Member States? - Lukas Vogel; Robert Kollmann; Marco Ratto; Werner Roeger; Jan in 't Veld (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
We estimate a three-country model using 1995 2013 data for Germany, the Rest of the Euro Area (REA) and the Rest of the World (ROW) to analyse the determinants of Germany s current account (CA) surplus after the launch of the euro. Our results suggest that the German surplus reflects a succession of distinct shocks. Mono-causal explanations of the surplus are thus insufficient. The most important factors driving the German surplus were positive shocks to the German saving rate and to ROW demand for German exports, as well as German labour market reforms and other positive German aggregate supply shocks. The key shocks that drove the rise in the German CA tended to worsen the REA trade balance, but had a weak effect on REA real activity. Our analysis suggests these driving factors are likely to be slowly eroded, leading to a very gradual reduction of the German CA surplus. An expansion in German government consumption and investment would raise German GDP and reduce the CA surplus, but the effects on the surplus would be weak.
Keywords: E30; F30; F40; 330